Occupational asthma caused by inhalation of surfactant composed of amines - Villar-Gómez, Ana; Muñoz, Xavier; Culebras, Mario; Morell, Ferran; Cruz, Maria-Jesus (Scandinavian Journal of Work, Environment & Health, 2009)
' ' OBJECTIVE ': 'Occupational asthma (OA) is highly prevalent in industrialized countries and nearly 400 causal agents of this condition have been described to date. This study aims to describe the case of a patient who developed OA secondary to exposure to a surfactant agent comprised of alkylamine ethoxylate and a mixture of alkyleneoxy and ethylenediamine. ' ' METHODS ': 'We present the case of a male worker in the meat industry suffering from OA resulting from exposure to a surfactant agent used to clean the animal carcass before it is quartered. We performed various tests on the individual, including: a chest computed tomography; total serum immunoglobulin E (IgE) and specific IgE tests against common pneumoallergens; pulmonary function studies; a methacholine test; and a specific inhalation challenge to the surfactant agent. ' ' RESULTS ': 'The tests confirmed the diagnosis of OA. ' ' CONCLUSIONS ': 'We discuss whether the amines present in the surfactant or the agent itself might be the cause of the condition. Because of the extensive use of surfactants in several types of industries, it is reasonable to think that their possible relationship with OA may have relevant health implications.
Keywords: amine; asthma; case report; cleaning product; inhalation; occupational asthma; specific inhalation challenge; surfactant; tensioactive agent